MAKING A WORK SAFETY AND SECURITY MAGAZINE INFORMATION-ORIENTED LABORATORY - Zulfa Munifah; Neneng Windayani; Sari Sari (Gunung Djati Conference Series, 2021)
This research was driven from a lack of understanding and awareness of information regarding the safety aspects of laboratory work. Thus causing the number of work accidents in the laboratory to be high. The method used is Design Based Research (DBR). Based1 on the results1 of the1 study, obtained magazine oriented information literacy products that present material about safety laboratory work with questions that refer to information literacy. General, this results of magazine validation are declared valid with an average calculation of 0.76 in the presentation of material; 0.73 in the language; and 0.74 in the magazine display. The test results show decent results with a percentage 86.5% in the presentation of material; 85% in the language; and 86% in the magazine display. This shows that magazine are very feasible to use as teaching materials for learning.